(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This paper explores the critical role of local governments in shaping public education, access to knowledge, and lifelong learning opportunities for their communities. Local governments are key players in the education sector, directly impacting the quality of education, the accessibility of learning resources, and the opportunities available for continuous learning. The study examines how local governments design, implement, and support educational policies to promote inclusive education, knowledge access, and lifelong learning. The research adopts a qualitative approach, using case studies and interviews with local government officials, educators, and community leaders to identify the key challenges and opportunities within the education systems. The findings reveal that while local governments play a pivotal role in expanding access to education, there are still significant barriers related to funding, infrastructure, and social inequalities. The paper proposes recommendations to improve local government involvement in enhancing public education and lifelong learning opportunities for all citizens.